Metabolites of 5F‐AKB‐48, a synthetic cannabinoid receptor agonist, identified in human urine and liver microsomal preparations using liquid chromatography high‐resolution mass spectrometry. Issue 3 (6th May 2014) - Holm, Niels Bjerre; Pedersen, Anders Just; Dalsgaard, Petur Weihe; Linnet, Kristian
<x xml:space="preserve">Abstract</x> New types of synthetic cannabinoid designer drugs are constantly introduced to the illicit drug market to circumvent legislation. Recently, N‐​(1‐Adamant​yl)‐​1‐​(5‐​fluoropentyl)‐​1H‐​indazole‐​3‐​carboxamide (5F‐AKB‐48), also known as 5F‐APINACA, was identified as an adulterant in herbal products. This compound deviates from earlier JHW‐type synthetic cannabinoids by having an indazole ring connected to an adamantyl group via a carboxamide linkage. Synthetic cannabinoids are completely metabolized, and identification of the metabolites is thus crucial when using urine as the sample matrix. Using an authentic urine sample and high‐resolution accurate‐mass Fourier transform Orbitrap mass spectrometry, we identified 16 phase‐I metabolites of 5F‐AKB‐48. The modifications included mono‐, di‐, and trihydroxylation on the adamantyl ring alone or in combination with hydroxylation on the N‐fluoropentylindazole moiety, dealkylation of the N‐fluoropentyl side chain, and oxidative loss of fluorine as well as combinations thereof. The results were compared to human liver microsomal (HLM) incubations, which predominantly showed time‐dependent formation of mono‐, di‐, and trihydroxylated metabolites having the hydroxyl groups on the adamantyl ring. The results presented here may be used to select metabolites specific of 5F‐AKB‐48 for use in clinical and forensic screening. Copyright © 2014 John Wiley & Sons, Ltd.